ANALISIS PELAKSANAAN KEGIATAN PENINGKATAN PERANAN WANITA MENUJU KELUARGA SEHAT SEJAHTERA (P2WKSS) DI DESA LIPAI BULAN KECAMATAN KERUMUTAN KABUPATEN PELALAWAN PERIODE 2012-2013 - Febry Arif Fadillah; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Development success is largely determind by the ability of officials in formulating policy or program to be implemented by government officials in the community groups that participate jointly implement programs or policies that have been decided who should be endorsed or supported by the existing infrastuctureWith the precision of government see the potential developed by a region, as well as the construction carried out did not result in new problems it is necessary environmental conditions been created for a well-ordered society with the creation of gender equality therein. This is necessary in order to avoid overlapping in the implementation of policies implemented.In this study, the method used is qualitative approach. Whereas the data analysis technique used is describing a situation or event. This research was conducted in Pelalawan district sub-district village Kerumutan Lipai Bulan. Whereas the object of this study in the implementation of an integrated program implemented in the village P2WKSS Lipai Bulan. With the focus on the development program launched by the government district seen from the factors that influence the success of the programs impelemented Lipai Bulan this village. Theory used is the theory advanced by Budi Winarno.After doing some research, the writer can see the success factors that are owned by the district respresented by agency child protection women’s empowerment and family planning in implementing an integrated program P2WKSS namely the availability of regulation, the district government’s cooperation with the private sector, adequate resources, facilities and infrastructure, then the last one is the budget. With these factors there is also a great good governance in the implementation of programs that do.Keywords: Implementation, program mechanism, gender mainstreaming.